Characterization and photocatalytic activity of Pd-doped ZnO nanoparticles synthesized by flame spray pyrolysis - C. Siriwong (2018)
Flame spray pyrolysis (FSP) was employed to synthesize the pure ZnO and palladium (Pd)-doped ZnO nanoparticles containing 0.25, 0.50, 0.75 and 1.0 mol% Pd. Pd is one of the most versatile and most widely applied as catalytic metal. Precursor solutions of zinc naphthenate and palladium (II) acetylacetonate were sprayed and combusted, resulting in crystalline and nanostructured particles. The crystalline phase, morphology and size of the nanoparticles were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The specific surface area of the nanoparticles was measured by nitrogen adsorption (BET analysis). The ZnO nanoparticles were observed as particles having the clear spheroidal, hexagonal and rod-like morphologies. The accurate sizes of these nanoparticles were in the range of 5-25 nm. The elements dispersion was determined by a mapping mode of scanning-transmission electron microscopy (STEM). The photocatalytic activity of ZnO samples were investigated by UV-induced degradation of methanol, glucose and sucrose in aqueous solutions in a photocatalytic reactor. The results showed that the photocatalytic activity of all Pd-doped ZnO nanoparticles were better than that of pure ZnO nanoparticles. In addition, 0.5 mol%Pd-doped ZnO nanoparticles showed the fastest response to the degradation of methanol, glucose and sucrose. © 2008 IEEE.